Effects of Nitrogen Application Strategies on Yield, Nitrogen Uptake and Leaching in Spring Maize Fields in Northwest China - Ying Wang; Jingjing He; Zongyuan Gao; Ruliang Liu; Yu Hong; Fang Wang; Xinping Mao; Tianxiang Xu; Lina Zhou; Jun Yi (Plants)
Nitrogen (N) is an essential nutrient for crop growth, as N fertilizer application regulates crop nitrogen uptake, affecting leaf photosynthetic rates, crop growth, and yield formation. However, both N deficiency and excess can reduce corn yields. Hence, optimizing the N fertilizer application strategy is crucial for crop production. In this study, a field plot trial with five N fertilization application strategies was conducted in the maize field from 2021 to 2022 in the Ningxia Yellow Irrigation District, Northwest China. These strategies contain zero N application rates (CK, 0 kg ha−1), the farmer practical N fertilizer application strategy (FP, 420 kg ha−1), the optimized N fertilizer application strategy (OPT, 360 kg ha−1), organic fertilizer and chemical fertilizer combination application (ON, 300 kg ha−1), and controlled-release N fertilizer and 33 urea application (CN, 270 kg ha−1). The maize yield and N balance under each treatment were investigated to propose the optimized N application strategy. The results showed that the CN treatment’s grain yield (15,672 kg ha−1) was the highest in both years, which was 109.97% and 8.92% higher than the CK and FP treatments, respectively. The apparent utilization rate and partial productivity of N fertilizer decreased with the increase in the N application rate. Also, the apparent utilization rate of N fertilizer in CN was 23.02%, 19.41%, and 13.02% higher than the FP, OPT, and ON, respectively. Applying controlled-release urea and organic fertilizers improved the physical and chemical properties of the soil, increased the organic matter content and soil fertility, and ultimately increased the spring maize yield. Meanwhile, the TN, NO3−-N, and NH4+-N concentrations in leaching water significantly correlated with the N application rate. With the extension of the maize growth period, the concentrations of TN, NO3−-N, and NH4+-N in leaching water gradually decreased. The N leaching amount in FP was the highest, while the CN was the lowest. The NO3−-N is the primary N leaching form, accounting for 46.78~54.68% of the TN leaching amount. Compared with the CN, the ON significantly increased the inorganic N content in the 0–40 cm soil layer, and it reduced the residual inorganic N content below 40 cm soil depths compared with FP and OPT treatments. Considering the relatively high spring maize yield and N utilization efficiency, as well as the relatively low N leaching amount and soil inorganic N residues, the ON and CN treatments with 270–300 kg ha−1 N application rate were the optimized N application strategies in the spring maize field in the study area.